2000
DOI: 10.1023/a:1005551903029
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The purpose of the study was to quantify gastric mucosal macrophages and define their association with the histopathologic features of stomach biopsies obtained from Helicobacter pylori-infected and uninfected children. Endoscopically obtained gastric biopsies from symptomatic children were independently evaluated by two groups of pathologists. Thirty children were evaluated; 14 were H. pylori-infected. H. pylori positivity was determined by hematoxylin and eosin (H&E), Giemsa, Warthin-Starry and an H. pylori-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…During H. pylori infection, macrophages are recruited to the gastric mucosa, where they contribute to the production of pro-inflammatory cytokines and chemokines [10], [11], [12], [13], [14], [15]. In addition, a recent study showed that liposome-mediated depletion of macrophages reduced gastric pathology in H. pylori -infected mice [16].…”
Section: Introductionmentioning
confidence: 99%
“…During H. pylori infection, macrophages are recruited to the gastric mucosa, where they contribute to the production of pro-inflammatory cytokines and chemokines [10], [11], [12], [13], [14], [15]. In addition, a recent study showed that liposome-mediated depletion of macrophages reduced gastric pathology in H. pylori -infected mice [16].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the H. pylori -induced gastric epithelial damage enables the bacteria to enter lamina propria and encounter macrophages7. Macrophages infiltration into gastric mucosa is detected in the H. pylori -infected patients8, which can function to capture the bacteria7. Both M1 and M2 macrophages are detected in gastric biopsy specimens isolated from H. pylori -infected patients, indicating the importance of macrophages in host defense against H. pylori 910.…”
mentioning
confidence: 99%
“…Gastric inflammatory protein levels were quantified in male mice, including macrophage-associated proteins given histiocytic activation occurs in H. pylori infection ( 32 , 35 , 36 ). Gastric protein levels of GM-CSF and M-CSF, which regulate macrophage differentiation, MCP-1, a key monocyte chemoattractant, and MIP-1α and MIP-2, inflammatory proteins produced by macrophages, were decreased in male mice coinfected with C. acnes followed by H. pylori compared to H. pylori monoinfection.…”
Section: Discussionmentioning
confidence: 99%